Gestión operativa y su incidencia en los procesos para la adquisición de bienes y servicios en la estación experimental tropical pichilingue iniap cantón mocache, año 2023 - Proaño Tovar, Johanna Annabell (2025)
Delays and deficiencies in the procurement processes of the public procurement department create operational limitations that impact the achievement of institutional objectives. For this reason, the research focused on evaluating the impact of operational management on the procurement processes of goods and services at the Estación Experimental Tropical Pichilingue of INIAP. The study utilized inductive, deductive, and statistical methods, which allowed for addressing the issue from different perspectives. Data was collected through interviews and surveys conducted with a representative sample of 55 individuals, selected from a total population of 87, including management, administrative staff, and operational technicians. The data obtained was analyzed using descriptive statistical tools. The results reflect both the strengths and weaknesses of the current process, providing key insights to design strategies that promote transparency and efficiency in the procurement of goods and services. Additionally, it was found that operational management faces significant limitations due to a lack of coordination between technical areas and the public procurement unit. Deficiencies in the planning, execution, and monitoring of the procurement process affect the achievement of institutional goals. Therefore, it is recommended to implement a continuous improvement system to promote the efficient procurement of goods and services at the Estación Experimental Tropical Pichilingue of INIAP.